2012
DOI: 10.1175/waf-d-10-05043.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tools Used for Monitoring and Forecasting Flash Floods in the United States

Abstract: This paper evaluates, for the first time, flash-flood guidance (FFG) values and recently developed gridded FFG (GFFG) used by the National Weather Service (NWS) to monitor and predict imminent flash flooding, which is the leading storm-related cause of death in the United States. It is envisioned that results from this study will be used 1) to establish benchmark performance of existing operational flash-flood prediction tools and 2) to provide information to NWS forecasters that reveals how the existing tools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 20 publications
3
57
1
1
Order By: Relevance
“…Meanwhile, real-time forecast systems that are based on hydrological models might exhibit an increased probability of system failures because of model instability, incorrect updating procedures, and error propagation (Martina et al, 2006). Under these circumstances, an early warning method that is based on a rainfall threshold can serve as a satisfactory auxiliary reference, as proposed by several past studies (Mogil et al, 1978;Schmidt et al, 2007;Norbiato et al, 2008;Gourley et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, real-time forecast systems that are based on hydrological models might exhibit an increased probability of system failures because of model instability, incorrect updating procedures, and error propagation (Martina et al, 2006). Under these circumstances, an early warning method that is based on a rainfall threshold can serve as a satisfactory auxiliary reference, as proposed by several past studies (Mogil et al, 1978;Schmidt et al, 2007;Norbiato et al, 2008;Gourley et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Schmidt et al (2007) proposed a raster-based method to derive a gridded FFG (GFFG) in a distributed manner. Gourley et al (2012) reported that FFG performs better than the GFFG, but the GFFG can detect the spatial variability.…”
Section: Introductionmentioning
confidence: 99%
“…This value is related to the characteristic of precipitation, soil moisture, and underlying surface (Diakakis 2011;Yucel 2015). Gourley et al (2012) evaluated Flash Flood Guidance (FFG) values and developed the gridded FFG used by the National Weather Service (NWS) to monitor and predict imminent flash flooding. Clark et al (2014) established the benchmark skill of the operational flash flood guidance (FFG) product used by NWS to forecast, monitor, and warn the public about dangerous flash flooding events.…”
Section: Research Status Of Flash Flood Early-warning Indexmentioning
confidence: 99%
“…Even if both observed flood databases (NWS Storm Data and SHAVE) do not provide a comprehensive identification of all flash-flood events with accurate spatiotemporal description, they enabled Gourley et al (2012) to conduct a detailed comparison of the performances of FFG and recently developed gridded FFG (GFFG) used operationally in the NWS. Also Calianno et al (2013) used these databases to classify the impacts of flash floods in relation with socio-spatial attributes (such as land use and population density) and to evaluate whether flash-flood forecasting tools (namely FFG, GFFG and DHM-TF) could differentiate such categories of impacts.…”
Section: Evaluation Mechanismsmentioning
confidence: 99%